(Ineffective) Messages to Encourage Recycling : Evidence from a Randomized Evaluation in Peru - Chong, Alberto (World Bank, Washington, DC, 2013)
There is growing interest in using messaging to drive prosocial behaviors, which contribute to investment in public goods. The authors worked with a leading nongovernmental organization in Peru to randomize nine different prorecycling messages that were crafted on the basis of best practices, prior evidence, and theories of behavioral change. Different variants emphasized information on environmental or social benefits, social comparisons, social sanctions, authority, and reminders. None of the messages had significant effects on recycling behavior. However, reducing the cost of ongoing participation by providing a recycling bin significantly increased recycling among enrolled households.